STRUCTURAL PROPERTIES OF Ba0.9Sr0.1TiO3 FERROELECTRIC MATERIALS - D.R.SAPATE (Innovare Journal of Sciences, 2020)
Objective: Ferroelectric materials are polar materials characterized by a transition to a paraelectric,nonpolar phase at a temperature at which their dielectric permittivity presents a maximum. Ferroelectric materials exhibit spontaneous polarization, the direction of which can be switched by applying an external electric field. Ferroelectric materials are a sub class of Pyroelectrics and Piezoelectrics. Materials and Methods: Ferroelectrics (Ba0.9Sr0.1TiO3) (BST) were prepared by a conventional standard double sintering ceramic method. The structural properties of ferroelectrics were investigated. Result: The X-ray diffraction analysis was carried out to find the planes and calculate the lattice parameters, X-ray density, bulk density, intensity of highest peak and porosity of the ferrite and ferroelectrics. Conclusion: The analysis of X-ray diffraction pattern shows that the prepared Ba0.9Sr0.1TiO3 sample possesses Pervoskite tetragonal spinel structure. No other impurity phase was detected.